Lexical Metaphors in Onang Onang of Bobby and Kahiyang Tortor Dance - Siti Rahma Ritonga; Anni Holila Pulungan; Didik - Santoso (Universitas Negeri Medan, 2020)
This study is concerned with the use of metaphors in onang onang of Bobby and Kahiyang tortor dance. The objectives of this study were to describe the types of lexical metaphors and to find the reasons of the use of lexical metaphors in onang onang of Bobby and Kahiyang tortor dance. This study was conducted by qualitative content anaylisis method. The data in this study is the lyric of onang onang in Bobby and Kahiyang tortor dance. Meanwhile, the data source is the video of onang onang of Bobby and Kahiyang tortor dance. The findings of this study showed that the types of lexical metaphor used in onang onang of Bobby and Kahiyang tortor dance were five concepts of lexical metaphors, namely noun noun, noun verb, noun adjective, circumstance preposition noun, and verb preposition noun. The reason of using metaphor in onang onang of Bobby and Kahiyang wedding ceremony were first, to embellish the language in the lyric of onang onang itself and second, in order to the lyrics can easily arousing the feelings or emotions of the audience who heard it when the onang onang is sung. Keywords: Lexical Metaphor; Onang Onang; Tortor Dance